Synthesis and Electronic Properties of Triperyleno[3.3.3]Propellanes: Towards Two‐Dimensional Electronic Structures. Issue 6 (4th February 2019) - Kodama, Takuya; Miyazaki, Shogo; Kubo, Takashi
Abstract: Threefold symmetric triperyleno[3.3.3]propellanes (TPRPs), which are composed of three perylene units peri ‐fused on [3.3.3]proppellane, have been synthesized and their electronic properties characterized. Unsubstituted TPRP assembles into two‐dimensional honeycomb‐like networks. TPRP displays a bathochromic‐shifted absorption band in its absorption spectrum and shows well‐separated one‐electron redox waves in a cyclic voltammogram, due to a homoconjugative interaction between perylene moieties. A radical cation species of tert ‐butyl substituted TPRP shows spin delocalization over the whole of the molecule, which is derived from effective overlap of HOMOs among three perylene moieties. Abstract : Three‐bladed propeller : D3h ‐ symmetric triperyleno[3.3.3]propellanes were synthesized and their electronic properties characterized. The propellane forms a honeycomb 2D molecular assembly in the solid state and shows strong intramolecular electronic coupling between perylene blades.